SEJARAH PERANG SALIB: SERANGAN KRISTEN DALAM PERANG SALIB: (History of the Crusades: Christian Attacks in the Crusades) - Aghistna Dwi Afriani; Arim Irsyadulloh Albin Jaya (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2025)
This research thoroughly analyzes the different assaults made by Christian forces during the Crusades (1096–1291), emphasizing the interplay of religious fervor and tactical motives in every military operation they conducted. The primary objective is to comprehend how theological narratives justified the Crusaders' violence and masscres and how they were viewed as divine will. Additionally, the research demonstrates that cities like Antioch were selected as targets not just for their religious importance, but also for their strategic importance along the logistical route to Jerusalem. The conclusion that extreme violence against Muslims was regarded as a sacred act rather than merely a military necessity is supported by an examination of modern chronicles, such as those of Raymond d'Aguilers and Peter Tudebode. This blend of spiritual impetus and geopolitical consideration formed a recognizable trend throughout the numerous Crusade campaigns, significantly affecting the relationship between the Western and Eastern worlds as well as demographic shifts. By using a historical-critical methodology, this research sheds light on the intricate interactions that fueled the Crusades and the ideological legacy they have left in contemporary times.